Population balance equation for collisional breakage: A new numerical solution scheme and its convergence - Kushwah, Prakrati; Das, Arijit; Saha, Jitraj; Bück, Andreas (Communications in Nonlinear Science and Numerical Simulation, 2023)
A new numerical method for the solution of population balance equation modeling nonlinear collisional breakage is presented. The new scheme is obtained by modifying the birth term of discretized equation. Allocation of new born particles to their neighboring cells plays a vital role towards the efficiency of proposed model. A detailed investigation on mathematical properties of the scheme, e.g., consistency and stability, is presented for different mesh types. It shown that the new scheme is moment-consistent and has first order convergence rate. A new finite volume scheme for collisional breakage is also presented to validate the efficiency of new scheme over several physics embedded test problems.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Collisional breakage; Consistency; Error analysis; Lipschitz stability; Sectional methods